Modern possibilities of antiepileptic therapy at the start of treatment of focal epilepsy - P. N. Vlasov (Эпилепсия и пароксизмальные состояния, 2021)
The report presents data on the evaluation of efficacy and tolerability, as well as the dynamics of epileptiform activity index in adolescents and adults with newly diagnosed focal epilepsy during lacosamide therapy.